Conjugation of Cisplatin Analogues and Cyclooxygenase Inhibitors to Overcome Cisplatin Resistance. Issue 1 (15th October 2014) - Neumann, Wilma; Crews, Brenda C.; Sárosi, Menyhárt B.; Daniel, Cristina M.; Ghebreselasie, Kebreab; Scholz, Matthias S.; Marnett, Lawrence J.; Hey‐Hawkins, Evamarie
Abstract Cyclooxygenase (COX) is an enzyme involved in tumorigenesis and is associated with tumor cell resistance against platinum‐based antitumor drugs. Cisplatin analogues were conjugated with COX inhibitors (indomethacin, ibuprofen) to study the synergistic effects that were previously observed in combination treatments. The conjugates ensure concerted transport of both drugs into cells, and subsequent intracellular cleavage enables a dual‐action mode. Whereas the platinum(II) complexes showed cytotoxicities similar to those of cisplatin, the platinum(IV) conjugates revealed highly increased cytotoxic activities and were able to completely overcome cisplatin‐related resistance. Although some of the complexes are potent COX inhibitors, the conjugates appear to execute their cytotoxic action via COX‐independent mechanisms. Instead, the increased lipophilicity and kinetic inertness of the conjugates seem to facilitate cellular accumulation of the platinum drugs and thus improve the efficacy of the antitumor agents. These conjugates are important tools for the elucidation of the direct influence of COX inhibitors on platinum‐based anticancer drugs in tumor cells.